Dichotic Perception of Lexical Tones in Cantonese-Speaking Congenital Amusics - Shao, Jing; Zhang, Caicai (Frontiers in Psychology, 2020)
Congenital amusia is an inborn neurogenetic disorder of musical pitch processing, which also induces impairment in lexical tone perception. However, it has not been examined before how the brain specialization of lexical tone perception is affected in amusics. The current study adopted the dichotic listening paradigm to examine this issue, testing 18 Cantonese-speaking amusics and 18 matched controls on pitch/lexical tone identification and discrimination in three conditions: nonspeech tone, low syllable variation and high syllable variation. For typical listeners, the discrimination accuracy was higher with shorter RT in the left ear regardless of the stimulus types, suggesting a left-ear advantage in discrimination. When the demand of phonological processing increased, as in the identification task, shorter RT was still obtained in the left ear; however, the identification accuracy revealed a bilateral pattern. Taken together, the results of the identification task revealed a reduced LEA or a shift from the right hemisphere to bilateral processing in identification. Amusics exhibited overall poorer performance in both identification and discrimination tasks, indicating that pitch/lexical tone processing in dichotic listening settings was impaired, but there was no evidence that amusics showed different ear preference from controls. These findings provided temporary evidence that although amusics demonstrate deficient neural mechanisms of pitch/lexical tone processing, their ear preference patterns might not be affected. These results broadened the understanding of the nature of pitch and lexical tone processing deficiencies in amusia.